Time and Space in Collaborative Information Seeking: The Clash of Effectiveness and Uniqueness - Gonzalez-Ibanez, R (2012)
Collaboration takes place at different time-space conditions. Past research has shown that these two dimensions may have different implications in the collaboration process, as well as on its outcomes, depending upon the task being performed. In collaborative information seeking (CIS), as a relatively new topic in information science, little is known about the effects of different temporal-spatial contexts. To address this, we conducted a user study involving 80 participants in 40 pairs, which were assigned to four experimental conditions, namely: co-located, remotely located with text chat, remotely located with audio chat, and asynchronous. Using quantitative methods, we investigated the effects of these conditions on communication, information synthesis, productivity, and user experience. Results regarding the space dimension suggest that information seeking behaviors of co-located users tend to overlap thus affecting their coverage of diverse and useful information.Conversely, when team members are remotely located, limited interaction allows them to work more independently, leading them to explore more diverse and useful information with the added value of less cognitive and affective load. With respect to the time dimension, we found that asynchronous collaboration enables participants to reach high levels of independency at the cost of effectiveness. These results provide practical implications about how various spatial-temporal contexts in CIS could influence factors such as productivity, efficiency, effectiveness, and uniqueness. Copyright 2012 Roberto González-Ibáñez, Muge Haseki, and Chirag Shah of Rutgers University.